Integration of Biomechanical and Biological Characterization in the Development of Porous Poly(caprolactone)-Based Membranes for Abdominal Wall Hernia Treatment. (9th December 2018) - Vozzi, Federico; Nardo, Tiziana; Guerrazzi, Ilenia; Domenici, Claudio; Rocchiccioli, Silvia; Cecchettini, Antonella; Comelli, Laura; Vozzi, Giovanni; De Maria, Carmelo; Montemurro, Francesca; Ciardelli, Gianluca; Chiono, Valeria
Abstract : Aims . Synthetic meshes are the long-standing choice for the clinical treatment of abdominal wall hernias: the associated long-term complications have stimulated the development of a new generation of bioresorbable prostheses. In this work, polycaprolactone (PCL) porous membranes prepared by solvent casting/porogen leaching of PCL/poly(ethylene glycol) (PEG) blends with different compositions (different PCL/PEG weight ratios and PEG molecular weights) were investigated to be applied in the field. An optimal porous membrane structure was selected based on the evaluation of physicochemical, biomechanical, and in vitro biological properties, compared to a reference commercially available hernia mesh (CMC). Findings . Selected PCL7-2i membranes, derived from PCL/PEG 70/30 (PCL: M w 70, 000-90, 000 Da; PEG: 35, 000 Da), showed suitable pore size for the application, intermediate surface hydrophilicity, and biomimetic mechanical properties. In vitro cell tests performed on PCL7-2i membranes showed their cytocompatibility, high cell growth during 21 days, a reduced production of proinflammatory IL-6 with respect to CMC, and a significant secretion of collagen type I. Conclusions . PCL7-2i membranes showed biomimetic biomechanical properties and in vitro biological properties similar to or even better than - in the case of anti-inflammatory behavior and collagen production - CMC, a commercially available product, suggesting potentially improved integration in the host tissue.